Algorithms for adult outpatient care of coronavirus disease 2019 (COVID-19) and its Assumption - M. A. Livzan; O. M. Drapkina; N. A. Nikolaev; Y. P. Skirdenko; R. N. Shepel; I. A. Viktorova; M. V. Kuznetsova; A. V. Mordyk; K. A. Andreev; V. G. Berezhnoy; M. V. Vershinina; A. V. Gorbenko; et al. (Кардиоваскулярная терапия и профилактика, 2021)
The paper presents algorithms for adult outpatient care of coronavirus disease 2019 (COVID-19) and its assumption.